2018
DOI: 10.1021/acs.jnatprod.7b00865
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Gramistilbenoids A, B, and C

Abstract: Stilbenes are biologically active metabolites of plants that have the potential to attenuate a broad range of human diseases. Gramistilbenoids are a class of natural products with a stilbene skeleton, isolated from the bamboo orchid ( Arundina graminifolia), and with significant cytotoxicity against cancer cell lines (NB4, A549, SHSY5Y, PC3, and MCF7). These are the first identified naturally occurring diphenylethylenes to possess a hydroxyethyl unit. However, some of these compounds are not abundant in nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…On the basis of our retrosynthetic analysis, our synthesis started with regioselective protection of the hydroxy groups of commercially available 2′,4′,6′-trihydroxyacetophenone (5) by treatment with methoxymethyl chloride (MOMCl) and N,Ndiisopropylethylamine (DIPEA) in dry dichloromethane (DCM) to give compound 6 in 90% yield. 18 O-Prenylation of compound 6 K 2 CO 3 as the base gave intermediate 7, which underwent microwave-assisted para-Claisen rearrangement to produce compound 8 in 89% yield. The selective deprotection of compound 8 under acidic conditions (2 N HCl) afforded mono-MOM-protected compound 9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the basis of our retrosynthetic analysis, our synthesis started with regioselective protection of the hydroxy groups of commercially available 2′,4′,6′-trihydroxyacetophenone (5) by treatment with methoxymethyl chloride (MOMCl) and N,Ndiisopropylethylamine (DIPEA) in dry dichloromethane (DCM) to give compound 6 in 90% yield. 18 O-Prenylation of compound 6 K 2 CO 3 as the base gave intermediate 7, which underwent microwave-assisted para-Claisen rearrangement to produce compound 8 in 89% yield. The selective deprotection of compound 8 under acidic conditions (2 N HCl) afforded mono-MOM-protected compound 9.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After 24 h, the cells were incubated with serum-free media containing each compound obtained from the in-house synthesized 1697 chemical diversity library (Dongguk Univ.) and a commercial 1,102 chemical library (Selleckchem) for 4 h. The in-house library contains synthesized chemicals composed of diverse chemotypes, including phenylthiophene, biphenyl 78 , benzofuran 79 82 , stilbenes 83 , 84 , aryloxyacetamide 85 94 , and sulfonamide 27 , 95 . After incubation, luciferase activity was detected using the nanoluciferase assay system following the manufacturer’s protocol (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Stilbenoids are widely found in plant varieties such as grapes, peanuts, sorghum, berries and spruce. [5] Due to their extensive physiological functions such as anti-cancer, antioxidation and hypolipidemic, they have received extensive attention. [6] Studies have shown that stilbenoid-maternal structure can intercept ultraviolet efficiently.…”
Section: Introductionmentioning
confidence: 99%